IMPLEMENTASI KURIKULUM 2013 DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 1 METRO - Safitri Mardiana; Sumiyatun Sumiyatun (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
The purpose of this research are 1) Describe the implementation of the curriculum in 2013 on teaching of history, 2) to explain the principal visual, history teacher, and students regarding the implementation of the curriculum 2013, 3) to formulate the factors that support and hinder the implementation of Curriculum 2013, Where this research is a study with qualitative research with descriptive approach. The data collection technique is to conduct in-depth interviews observation, documentation, and questionnaire. Data analysis performed by the researchers is to perform the first reducing the data after it's done after the presentation of data that do verifikasion. The results showed that a history teacher in the eleventh grade curriculum mengimplemntasikan 2013 quite well. This can be seen with the preparation of RPP conducted by the teacher never mind in accordance with the demands contained in the Minister of Education and Culture of the Republic of Indonesia 103 2014. In the process of learning history teachers already apply learning with the scientific approach which consists of observing, ask, gather information, associate and communicate. This approach aims to guide students actively following the learning process. Besides scoring system using authentic assessment includes an assessment of attitudes, knowledge and skills.